Repotenciación y actualización de los tableros didácticos de instalaciones residenciales existentes en el taller de electricidad del Área de la Energía, las Industrias y los Recursos Naturales no Renovables. - Granda Castillo, Roberth Leonardo (2010)
This technical report we have done under the title of "repowering BOARDS AND UPDATE OF EXISTING RESIDENTIAL FACILITIES TEACHING IN THE WORKSHOP AREA ELECTRIC POWER, industries and non-renewable resources" that seeks to improve the same techniques Learning for efficient practical development of students. This topic was chosen by the need to give our fellow new tools and systems for practical improvements to the banks for residential electrical installations. For proper implementation of this project is: To emphasize the importance of electrical installation practices in the workplace, to characterize the basic circuits identified in the work practice and deepen understanding of the different types of electrical connections. With this the student is able to perform an efficient work in their occupational field. Finally, for a better job let us leave the electrical components used in the different practices carried out within this projet.